2021
DOI: 10.5812/thrita.100105
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots Application in Neurodegenerative Diseases

Abstract: : Quantum dots (QDs) are nanoparticles (NPs) with electronic and optical properties such as emitting bright light and fluorescence. They also carry specific characters such as photostability, high quantum yield, high emission, and size-turnable. Nowadays, a great interest is given to the extensive use of theranostic-NPs for sensing and imaging, as well as drug delivery. Moreover, QDs may yield great potential for the diagnosis and treatment of various central nervous system (CNS) diseases (e.g., Parkinson’s di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…One of the most prevalent noninfectious diseases is related to the CNS (central nervous system) disorders and tumors, which have more than one Frontiers in Pharmacology frontiersin.org barrier for compound delivery including the BBB (blood-brain barrier) and cell membrane. Recently, various vectors such as gold NPs or Quantum Dots (QDs) help the BBB transfer of the biomolecules (Hasannejadasl et al, 2020;Hasannejad-Asl et al, 2022). But however, these vectors have limitations (Swain et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prevalent noninfectious diseases is related to the CNS (central nervous system) disorders and tumors, which have more than one Frontiers in Pharmacology frontiersin.org barrier for compound delivery including the BBB (blood-brain barrier) and cell membrane. Recently, various vectors such as gold NPs or Quantum Dots (QDs) help the BBB transfer of the biomolecules (Hasannejadasl et al, 2020;Hasannejad-Asl et al, 2022). But however, these vectors have limitations (Swain et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some varieties of conjugated QDs are suitable carriers and are valuable for traversing the BBB in a variety of applications, including accurate imaging and detection of brain illnesses. The primary factor for transferring across the BBB is the particle surface, not the NPs’ size or chemo-electric charge [ 114 ]. One study synthesized QDs from the extract of the flower of Clitoria ternatea and observed that the learning and memory capacity of treated rats improved in the radial arm and Morris water maze assays.…”
Section: Nanomedicinementioning
confidence: 99%
“…• Piezoelectric energy harvester [35] Cryotechnics • Cryogenic-temperature thermodynamically Suppressed and strongly confined quantum dots [36] • SQUIDS (superconducting quantum interference devices) [37] Mechanics • Quantum-dot array with self-aligned electrodes [38] • Reversible adhesion via quantum dots [39] • Reduction of friction [40] Magnetics • Quantum-dot cellular automata [41] • Multimodal imaging [42] Sensorics • Data acquisition in antagonistic surroundings and media [43] • Telemetry monitoring via PDA [44] • Optical and electrochemical (bio)analytical sensors [45] Chemistry • Drift-diffusion [46] • Carbon dots are in contrast to corrosion inhibitors [47] • Resistive-based gas sensors [48] Biomedicine • Biocompatible implant coating [49] • Neurological sensors [50] New materials • Metastable phases/metallic glasses: Mn 2+ -doped CdS quantum dots in a silicate glass [51] Metal-doped PbSe quantum dots in silicate glasses [52] • Low-noise GaAs quantum photonics [53] • Ultra-stable carbon quantum dots [54] (Alternative) Energies…”
Section: Field Application With Examplesmentioning
confidence: 99%